2008
DOI: 10.1037/0021-9010.93.5.1104
|View full text |Cite
|
Sign up to set email alerts
|

When employees strike back: Investigating mediating mechanisms between psychological contract breach and workplace deviance.

Abstract: In this article, psychological contract breach, revenge, and workplace deviance are brought together to identify the cognitive, affective, and motivational underpinnings of workplace deviance. On the basis of S. L. Robinson and R. J. Bennett's (1997) model of workplace deviance, the authors proposed that breach (a cognitive appraisal) and violation (an affective response) initiate revenge seeking. Motivated by revenge, employees then engage in workplace deviance. Three studies tested these ideas. All of the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

23
326
0
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 343 publications
(354 citation statements)
references
References 56 publications
(124 reference statements)
23
326
0
5
Order By: Relevance
“…Consistent with that, it has been shown that that PCB is negatively related to job satisfaction (Raja, Johns & Ntalianis, 2004), intention to stay in the organization (Turnley & Feldman, 2000), job performance (Johnson & O'Leary-Kelly, 2003), trust in the organization (Zhao et al, 2007), organizational citizen behaviors (Restubog, Bordia & Tang, 2007) and organizational commitment (Zhao et al, 2007). At the same time, PCB was shown to be positively correlated with counterproductive work behaviors (Bordia, Restubog & Tang, 2008), absenteeism and organizational cynicisms (Johnson & O'Leary-Kelly, 2003).…”
Section: Introductionsupporting
confidence: 65%
“…Consistent with that, it has been shown that that PCB is negatively related to job satisfaction (Raja, Johns & Ntalianis, 2004), intention to stay in the organization (Turnley & Feldman, 2000), job performance (Johnson & O'Leary-Kelly, 2003), trust in the organization (Zhao et al, 2007), organizational citizen behaviors (Restubog, Bordia & Tang, 2007) and organizational commitment (Zhao et al, 2007). At the same time, PCB was shown to be positively correlated with counterproductive work behaviors (Bordia, Restubog & Tang, 2008), absenteeism and organizational cynicisms (Johnson & O'Leary-Kelly, 2003).…”
Section: Introductionsupporting
confidence: 65%
“…The purpose of the current study was not to identify the reasons behind why employees held specific relationship perceptions, rather how the relationship perceptions were used in making sense of promise experiences and emotion. These descriptive differences in contract perceptions have previously been linked to differences in perceptions of contract violation and important organisational outcomes, such as; job satisfaction, performance, and workplace deviance (Bordia et al, 2008;Raja et al, 2011). The findings suggest that those who perceive a more socio-emotional relationship with their organisation are more likely to perceive non-fulfilment of their contract and experience more negative consequences.…”
Section: Introductionsupporting
confidence: 47%
“…It has, for example, been found that perceiving a contract violation can mediate the effect of contract breach perceptions on employee deviance, commitment and trust towards the organisation (Bordia et al, 2008;Dulac et al, 2008). Essentially, what much of the research focussing on emotion within psychological contract relationships has come to highlight is not only are cognitive perceptions influential in the attitudes and behaviours of employees but so too are emotional perceptions and experiences.…”
Section: Introductionmentioning
confidence: 99%
“…Deviance is driven by specific cognitions such as thoughts of vengeance or retaliation or for personal gain [24], [25]; [26]. Deviance is also driven by the need to express emotions of anger or frustration [27].…”
Section: Workplace Deviancementioning
confidence: 99%